Myc. ra-wa-ke-ta and Dor. λᾱγέτᾱς: Diachronic Semantics and Literary History - Zhang, Chengzhi (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2025)
This article examines the use of the Mycenaean titular term ra-wa-ke-ta 'leader of the people' (spelling lāwāgetās , continued mainly as Dor. λᾱγέτᾱς) in post-Mycenaean Greek literature, demonstrating the textual and semantic diachrony of this culturally important term through a detailed survey of its usage in the classical period in comparison with the Linear B materials. Following its peculiar absence in Homer and early epics, in Ibycus and Pindar the word lāwāgetās exhibits a semantic shift from its administrative and militaristic denotation as shown in the palace documents to being chiefly used as an epithet for mythical and heroic figures. The word is further attested in Sophocles fr.221 where the title is applied to a female character. We will conclude the discussion with a brief look at what traces of λᾱγέτᾱς are preserved in names and lexicography before it finally disappeared in the extant Greek materials